A Modular Prussian Blue Nanozyme‐Based Microneedle Platform With Flexible Therapeutic Formulations for Localized Treatment of Traumatic Brain Injury - Xiang Wang; Ge Gao; Jinhua Li; Yilong Wang (Advanced Healthcare Materials, 2026)
ABSTRACT Secondary injury after traumatic brain injury (TBI) is characterized by excessive reactive oxygen species (ROS) production and persistent neuroinflammation, which remain difficult to control using a single therapeutic agent. Herein, a dissolvable microneedle platform based on Prussian blue (PB) nanoparticles was developed to locally deliver curcumin (Cur) or edaravone (EDA) into injured brain tissue through a transiently disrupted blood–brain barrier. The microneedles were fabricated from hyaluronic acid/carboxymethyl chitosan (HCMN) using a low‐temperature multilayer drying process while maintaining the structural integrity of PB nanoparticles. Acting as both ROS‐scavenging nanozymes and drug carriers, PB nanoparticles enabled flexible incorporation of different therapeutic agents within the same delivery platform. In vitro and in vivo studies showed that HCMN/PB/Cur exhibited greater anti‐inflammatory activity under relatively mild pathological conditions, whereas HCMN/PB/EDA displayed stronger antioxidant capacity under higher oxidative stress. These results suggest that different therapeutic formulations may be preferable under distinct pathological conditions while preserving the same delivery platform. This microneedle system provides a localized delivery approach and offers greater flexibility for formulation selection in the treatment of acute TBI.